Contribution of Fresh Submarine Groundwater Discharge to the Gulf of Alaska - A. A. Russo; D. F. Boutt; L. A. Munk; J. Jenckes (Water Resources Research)
Abstract High latitude mountain environments are experiencing disproportionately adverse effects from climate change. The Gulf of Alaska (GoA) region is an embodiment of this change, particularly concerning a shifting hydrologic balance. Even so, the magnitude and contribution of fresh submarine groundwater discharge (fresh SGD) remains virtually unexplored within the region, though it has gained increasing attention globally due to its chemical significance and influence on coastal ecosystems. Here we provide the first regional estimates of fresh SGD to the GoA using two established water balance approaches. This is an effective way to distinguish the contribution of terrestrially derived fresh SGD, rather than the more commonly quantified total SGD which includes discharge that is driven by marine forces such as sea‐level oscillations and density gradients. We compare the approaches and assess their capabilities in computing the magnitude of fresh SGD over a large regional scale. Mean annual fresh SGD flux ranges between 26.5 and 86.8 km3 yr−1 to the GoA, equivalent to 3.5%–11.4% of the total freshwater discharge. Contributions are highest in the Southeastern panhandle and lowest in the Cook Inlet basin, with the highest area normalized contribution occurring in the Prince William Sound. Fresh SGD exhibits high spatial and temporal variability throughout the region. Although freshwater discharge to the GoA is investigated considerably, the importance of fresh SGD has, thus far, been overlooked.